2013
DOI: 10.1159/000350102
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized Low-Density Lipoprotein Induces Inflammatory Responses in Cultured Human Mast Cells Via Toll-Like Receptor 4

Abstract: Background/Aims: Oxidized low-density lipoprotein (ox-LDL) is a powerful atherogen. Toll-like receptor 4 (TLR4) has a pathophysiological role in regulating inflammatory responses and atherosclerosis. Mast cells can infiltrate into the atheromatous plaque and secrete various pro-inflammatory cytokines, which significantly amplify the atherogenic processes and promote plaque vulnerability. Small interfering RNA (siRNA) is an effective method to silence the target genes. We evaluated whether ox-LDL-induced inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 43 publications
2
32
0
1
Order By: Relevance
“…Importantly, upregulation of LTB4 is also associated with enhanced phosphorylation, and hence activation, of ERK1/2. These observations suggest a mechanism that is consistent with findings from human and animal studies on the pathology of hypercholesterolemia- induced inflammation [12]. …”
Section: Discussionsupporting
confidence: 87%
“…Importantly, upregulation of LTB4 is also associated with enhanced phosphorylation, and hence activation, of ERK1/2. These observations suggest a mechanism that is consistent with findings from human and animal studies on the pathology of hypercholesterolemia- induced inflammation [12]. …”
Section: Discussionsupporting
confidence: 87%
“…In addition, the supernatant of RRx-001-incubated RBCs switched the TAM phenotype from M2 to M1 [19]. It is hypothesized that this switch occurs as a result of the catabolism of the lipid-rich RRx-001-modified red blood cell, since oxidized low-density lipoprotein is known to activate macrophages through the toll-like receptor 4 [27]. These M1 repolarized TAMs, which express proinflammatory cytokines such as tumor necrosis factor alpha, interleukin-6, and interferon gamma, stimulate the adaptive arm of the immune system as demonstrated by the infiltration of CD8 + T cells on patient biopsies.…”
Section: Lymphocytic Infiltration Of the Tumormentioning
confidence: 99%
“…TLR4 has been demonstrated to mediate myocardial ischemia reperfusion injury, maladaptive left ventricular remodeling and increased infarct size after myocardial infarction[13, 14, 24, 25]. Some research findings suggest that the activation of TLR4 signaling pathway is considered to be a promising therapeutic target for the treatment of atherosclerotic cardiovascular diseases[16, 26, 27]. In the present study, we revealed that the mRNA and protein levels of TLR4 were up-regulated after CME in rats.…”
Section: Discussionmentioning
confidence: 99%